2018
DOI: 10.1089/mdr.2017.0306
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Macrolide Resistance Among Group A Streptococci in Serbia and Clonal Evolution of Resistant Isolates

Abstract: In Serbia, the frequency of macrolide-resistant group A streptococci (MRGASs) increased significantly from 2006 to 2009. MRGAS analysis in 2008 revealed the presence of three major clonal lineages: emm75/mefA, emm12/mefA, and emm77/ermTR. The aim of the present study was to determine the prevalence of macrolide resistance and to evaluate variations in the clonal composition of MRGASs. The study included 1,040 pharyngeal group A streptococci collected throughout Serbia, which were tested for antimicrobial susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…Over the past 20 years, there have been studies showing similar clonal distribution of the multiresistant emm28 clone in other European countries, such as Spain, France, and Belgium [18][19][20]. The current work showed that macrolide-resistant isolates carrying the ermA gene are predominantly presented in genotypes emm77 and emm12, similar to the results from earlier Serbian studies [21].…”
Section: Discussionsupporting
confidence: 87%
“…Over the past 20 years, there have been studies showing similar clonal distribution of the multiresistant emm28 clone in other European countries, such as Spain, France, and Belgium [18][19][20]. The current work showed that macrolide-resistant isolates carrying the ermA gene are predominantly presented in genotypes emm77 and emm12, similar to the results from earlier Serbian studies [21].…”
Section: Discussionsupporting
confidence: 87%